The role of socially prescribed perfectionism in the link between perceived racial discrimination and African American adolescents’ depressive symptoms - Lambert, Sharon F. (2014)
Research examining the social origins of perfectionism has focused on negative evaluative experiences in the family, with less attention to negative social evaluations in other contexts and situations relevant for African American adolescents. The experience of racial discrimination is common for African American youth, and may trigger maladaptive perfectionistic beliefs if the youth perceive that they do not meet others’ standards (socially prescribed perfectionism) or internalize discriminatory messages. Thus, the present study examined longitudinal associations among racial discrimination, socially prescribed perfectionism, and depressive symptoms among a community sample of urban and predominantly low income African American adolescents (n = 492; 46.7% female). In each of grades 7, 8 and 9, participants reported their experiences with racial discrimination, perfectionistic beliefs, and depressive symptoms. Analyses revealed that experiences with racial discrimination in grade 7 were associated with socially prescribed perfectionism in grade 8 which, in turn, was linked with depressive symptoms in grade 9. Results suggest that prospective associations between the experience of racial discrimination and depressive symptoms are due, in part, to increased socially prescribed perfectionism. Implications for interventions targeting depression in African American are discussed.